Good Governance in the Era of Global Neoliberalism Conflict and depolitisation in Latin America, Eastern Europe, Asia and Africa - Jolle Demmers,, Alex E.Fernández Jilberto and Barbara Hogenboom (Routledge 11 New Fetter Lane, 2004)
At the dawn of the twenty-first century world politics is (once again) framed in terms of Good and Evil. The Forces of Freedom are fighting the Axes of Evil, while Civilization and Enlightenment are placed opposite Fundamentalism, Darkness and Barbarism. As is often the case, these words hide complex and ambiguous realities. The recipe for ‘freedom’, for instance, as proclaimed by Western powers and International Financial Institutions (IFIs) based on globalisation and market deregulation, is often seen as ‘market fundamentalism’ by developing countries. This is perhaps the greatest paradox of our times: the implementation of liberalism by force. This volume deals with the complexities and paradoxes surrounding one of the ‘Goods’ in contemporary development discourse: Good Governance. During the 1990s, the IFIs refashioned their somewhat worn-out discourse on the salutary effects of the free market by a strong emphasis on poverty reduction, transparent governance, human rights and democracy. Put under one heading, this new discourse was called Good Governance. And indeed, it seemed to proclaim only ‘the good’. It aimed to help countries reach economic prosperity, ensure the rule of law, improve the efficiency and accountability of their public sectors and tackle corruption. Good Governance was to confront the Bad Governance of many developing countries’ administrations. It was this Bad Governance that was held responsible for the disappointing results of the structural adjustment programmes of the 1980s and the rise of the parallel economy, poverty and income disparities in recently ‘neoliberalised’ countries. However, this book tells a different story. By making use of a wide variety of casestudies from various developing countries and post-communist states, this edited collection critically analyses the causes and effects of neoliberal restructuring and the policy of Good Governance that went with it. It shows how, in the encounter with national and local contexts, the recipe of Good Governance produced unexpected and often unwanted outcomes. The Good Governance approach entails an essentially depoliticised notion of governance, insulating governance from the actual political process: the struggles for power, control over resources, as well as access to the decisionmaking process. Apart from many differences and specificities, the case studies in this book show how the neoliberal recipe encouraged new forms of division, inequality and instability. In addition, the book unmasks the Good Governance solution embraced by the IFIs and many donor countries and lays bare its essentially neoliberal agenda.